Injectable hydrogels

By developing an injectable crosslinking hydrogel, using the crosslinking technology of oxidized nanocrystalline cellulose and gelatin peptide chains, the problem of difficult to effectively treat pathological joints in the prior art is solved, and direct injection into the joints is achieved Effective pain relief and mobility improvement effects.

CN119451709APending Publication Date: 2025-02-14ALLEGRO NV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380045837.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-06-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat pathological joints, especially those with arthritis, and traditional 3D printed stents require surgical implantation, which has a long recovery time and may lead to body rejection or limited therapeutic effects.

Method used

An injectable crosslinked hydrogel containing oxidized nanocrystalline cellulose and gelatin peptide chains was developed, formed by partial crosslinking of imine, which can be highly miscible and good viscoelastic properties in synovial fluid, and directly injected into the pathology. in the sexual joints.

Benefits of technology

The hydrogel can effectively restore the viscoelastic properties of the joint, relieve pain, improve mobility, and due to its stable colloidal form, it can limit inflammation and restore mobility of damaged joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451709A_ABST
    Figure CN119451709A_ABST
Patent Text Reader

Abstract

The invention provides an injectable hydrogel, the injectable hydrogel comprises oxidized nanocrystalline cellulose, a gelatin peptide chain, and the oxidized nanocrystalline cellulose and the gelatin peptide chain are cross-linked.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an injectable hydrogel, a method for preparing the injectable hydrogel, and the use of the injectable hydrogel for treating pathological joints (eg, those suffering from diseases such as arthritis). Background Art

[0002] Joints or joint motion are essential for the mobility of humans and animals. They are filled with synovial fluid and include articular cartilage as a complex, nonlinear, viscoelastic and anisotropic material that is subjected to millions of joint load cycles over decades of wear. Pathological joints may cause severe pain and reduced mobility and therefore lead to a severe degradation of the quality of life of the affected animal or human. For example, pathological joints may have different injuries or diseases, such as arthritis, for example rheumatoid arthritis, osteoarthritis or other forms of arthritis, as well as cartilage degeneration, cartilage damage or subchondral defects, resulting in reduced mobility and chronic pain.

[0003] 3D printing has recently been developed in order to obtain custom-made scaffolds to be implanted in damaged joints (e.g. due to accidents or trauma). However, the damaged joint must be opened in order to implant the printed scaffold therein, which requires a laborious surgical procedure and may result in a long recovery time for the patient, with the risk that the implant may be rejected by the body or result in deceptive results (such as limited mobility improvement or limited pain relief). In addition, the printed scaffolds are not suitable for curing joint diseases such as osteoarthritis.

[0004] Arthritis, such as osteoarthritis (OA), is a musculoskeletal disorder that is the largest cause of disability in the world. Although OA is often referred to as a joint disease with cartilage damage and loss, OA is a more diverse disease with a complex pathogenesis that affects all tissues within the joint. The main features of OA include progressive loss of articular cartilage tissue, inflammation of synovial tissue, disruption of synovial fluid characteristics, subchondral bone sclerosis, and the formation of osteophytes at the joint margins, which leads to chronic pain, joint stiffness, and ultimately impaired mobility.

[0005] Hydrogels are known in the art. For example, CN 110760103 relates to a viscoelastic hydrogel and its preparation method and application. Balakrishnan et al., Journal of Materials Chemistry B 2013, 1, 5564, disclose borate-assisted Schiff base formation to produce in situ gelling hydrogels. If these hydrogels are disclosed for cartilage regeneration, they are not suitable for relieving pain and increasing mobility of arthritic joints. Summary of the invention

[0006] The present disclosure relates to an injectable hydrogel comprising:

[0007] ●Oxidized nanocrystalline cellulose,

[0008] ● Gelatin peptide chain,

[0009] The oxidized nanocrystalline cellulose and the gelatin peptide chain are cross-linked.

[0010] Due to the very high miscibility of the hydrogel in synovial fluid and its favorable viscoelastic properties, this hydrogel can be injected into pathological joints, for example, in joints suffering from arthritis such as type I OA, to restore the viscoelastic properties of the joint and relieve pain. Alternatively, the injectable hydrogel of the present invention can be injected into other parts of mammals, such as in damaged eyes. The gelatin peptide chain may not be functionalized, that is, it only includes naturally occurring parts. The oxidized nanocrystalline cellulose may include an aldehyde moiety or may have a reactive part that is essentially composed of an aldehyde moiety. The hydrogel can then be prepared in the form of a stable colloid of gel particles in water buffered at physiological pH.

[0011] Advantageously, the oxidized nanocrystalline cellulose and the gelatin peptide chains are cross-linked by imine moieties. The imine or aldimine moieties may preferably be produced by direct reaction (e.g., by Schiff base reaction) of the oxidized nanocrystalline cellulose with the unmodified gelatin peptide chains. Therefore, a cross-linked hydrogel of the present invention may be obtained without the use of bridges or linkers.

[0012] Advantageously, the injectable hydrogel includes a buffer to maintain the pH of the injectable hydrogel at 7 to 8, preferably 7.2 to 7.6. For example, the buffer is Dulbecco's phosphate buffered saline (DPBS), but other buffers close to or within the desired pH range are contemplated. The buffer allows for increased biocompatibility of the injectable hydrogel when injected into a joint. The buffer may also contribute to an efficient cross-linking reaction.

[0013] Advantageously, the concentration in the composition before the gelatin peptide chains are cross-linked is 1.0 weight / volume% to 2.5 weight / volume%, preferably 1.5 weight / volume% to 2.1 weight / volume%, and most preferably 1.7 weight / volume% to 1.9 weight / volume%. Alternatively or in combination, the concentration of the oxidized nanocrystalline cellulose before cross-linking is 0.1 weight / volume% to 0.5 weight / volume%, preferably 0.2 weight / volume% to 0.4 weight / volume%, and most preferably 0.3 weight / volume%. The composition resulting in effective cross-linking and the hydrogel of the present invention can be obtained by a combination of oxidized nanocrystalline cellulose and gelatin peptide chains at any of the above concentrations.

[0014] Advantageously, the injectable hydrogel comprises 0.5 weight / volume % to 2.5 weight / volume % of cross-linked oxidized nanocrystalline cellulose and gelatin (i.e., gel fraction), preferably 0.8w / v% to 2w / v%, such as 1.5w / v% or 1.9w / v%. In other aspects, the injectable hydrogel may have a concentration of 0.1 (w / v)% to 10.0 (w / v)% or 0.5 (w / v)% to 5.0 (w / v)%. These concentrations of hydrogels may allow for easy and painless injection into pathological joints while effectively restoring mobility.

[0015] Advantageously, the injectable hydrogel has an elastic modulus at 0.1 Hz to 10.0 Hz of 10.0 Pa to 220.0 Pa, preferably 50.0 Pa to 200.0 Pa, and most preferably at most 80.0 Pa, for example 120.0 Pa. Such an elastic modulus allows for an optimal treatment of pathological joints.

[0016] Advantageously, the injectable hydrogel has a loss modulus at 0.1 Hz to 10.0 Hz of less than 10.0 Pa, preferably less than 9.0 Pa. Such a loss modulus allows optimal treatment of pathological joints, allowing restoration of a high level of mobility. For example, the loss modulus may be at least 5.0 Pa, at least 6.0 Pa or at least 7.0 Pa at 0.1 Hz to 10.0 Hz.

[0017] Advantageously, the ratio of the loss modulus to the elastic modulus (loss tangent, tan δ) of the injectable hydrogel is greater than 10 at 0.1 Hz. 5 And greater than 10 at 10.0Hz 3 Such a ratio allows optimal restoration of the viscoelastic properties of the pathological joint.

[0018] Advantageously, the complex viscosity of the injectable hydrogel is lower than 1.0 MPa.s, preferably lower than 0.9 mPa.s, more preferably lower than 0.8 mPa.s or lower than 0.7 mPa.s.

[0019] Advantageously, the injectable hydrogel has a cross-linking degree of 25% to 60%, preferably 38% to 51%, and most preferably 42% to 49%. A higher degree of cross-linking may render the hydrogel difficult to inject and may have a negative impact on pathological joints. A lower cross-linking rate may not heal or relieve pathological joints.

[0020] Preferably, the injectable hydrogel is sterile and / or homogeneous, without any aggregates, insoluble particles or solid phases. In addition, when mixed with synovial fluid, the injectable hydrogel can be completely homogeneous and / or isotropic, i.e., forming a stable colloid without solids or supernatants, so as to limit inflammation and restore mobility to damaged joints. Once cross-linked, the hydrogel can be directly injected.

[0021] Another aspect of the present disclosure is a method of preparing an injectable hydrogel according to any one of the preceding claims, the method comprising the steps of:

[0022] - Dilute oxidized nanocrystalline cellulose in pyrogen-free water

[0023] - Add gelatin peptide chains to diluted oxidized nanocrystalline cellulose at room temperature

[0024] -Reacting gelatin peptide chains with oxidized nanocrystalline cellulose.

[0025] The above method allows obtaining the hydrogel of the present invention at limited cost. If the gelatin peptide chains are added at low temperature, the gelatin peptide chains may have a helical conformation, resulting in a non-uniform hydrogel and preventing safe injection.

[0026] Advantageously, the reaction step is carried out for 10 to 25 hours and / or at room temperature, for example 15° C. to 25° C. Higher temperature cross-linking reactions may prevent effective cross-linking reactions. Low temperature cross-linking reactions may result in non-uniform hydrogels.

[0027] Advantageously, the reaction step may be performed at a slightly alkaline pH, for example greater than 7 to at most 8, preferably 7.2 to 7.6. A pH buffer may be used, for example a DPBS buffer, for example without stirring.

[0028] Advantageously, the gelatin peptide chains are prepared by a dilution step in pyrolyzed water at 37° C., and then the diluted gelatin peptide chains are cooled to room temperature, for example 20° C. or at least between 15° C. and 25° C. This allows for optimal dilution of the gelatin peptide chains and prepares the gelatin peptide chains for addition to the nanocrystalline cellulose.

[0029] Another aspect of the present disclosure is a medical syringe filled with the above-mentioned injectable hydrogel. Such a medical syringe is conducive to rapid injection into pathological joints such as those suffering from OA. The medical syringe can be pre-filled, that is, filled in the factory before delivery to patients and medical staff.

[0030] Preferably, the medical syringe comprises a single barrel defining a reservoir containing the hydrogel (i.e. after the cross-linking reaction) and a stopper closing the end of the barrel, the stopper being removable within the barrel. The medical syringe may preferably comprise a needle and / or a needle adapter for injecting the injectable hydrogel directly into the pathological joint. The needle may be in the range of 27 to 17 gauge, preferably 27 to 19 gauge, for example 25 to 21 gauge. The hydrogel may be stored in the syringe and / or injected with the syringe as a stable colloid in water buffered to physiological pH (e.g. pH = 7.2 to 7.4).

[0031] Another aspect of the present disclosure is the use of the above-described injectable hydrogel for alleviating the symptoms of osteoarthritis, for example in a mammal such as a horse or a human.

[0032] Another aspect of the present disclosure is a method of treating or healing a pathological joint, in particular a joint suffering from OA, comprising the steps of providing an injectable hydrogel as disclosed above and injecting the injectable hydrogel into the pathological joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Other advantages and preferred embodiments of the present disclosure will become apparent from the following detailed description and accompanying drawings, in which:

[0034] Figure 1 The elastic modulus (G') and viscous modulus (G") of synovial fluid extracted from normal and pathological midcarpal joints of horses are shown as a function of frequency.

[0035] Figure 2 A schematic reaction for preparing nanocrystalline cellulose is shown.

[0036] Figure 3 Several possible sugar units of nanocrystalline cellulose after oxidation reaction are shown.

[0037] Figure 4 The expanded formula of typical amino acids in the gelatin peptide chain is shown.

[0038] Figure 5 The elastic (G') and viscous (G") moduli of 2% (w / v) hydrogels according to the present disclosure are shown as a function of frequency.

[0039] Figure 6 The loss factor (tan δ) and complex viscosity of 2% (w / v) hydrogels are shown.

[0040] Figure 7 Shown are the elastic (G') and viscous (G") moduli of pathological synovial fluid extracted from the intercarpal joint (OA SF) and the same pathological synovial fluid mixed with 10% volume / volume hydrogel 2.0% (w / v) as a function of frequency.

[0041] Figure 8 The elastic (G') and viscous (G") moduli of pathological synovial fluid (OA SF + 10% hydrogel) mixed with 10% volume / volume hydrogel 2.0% (w / v) and normal synovial fluid extracted from the intercarpal joint of horses (OA SF) are shown as a function of frequency.

[0042] Fig. 9Shown are shear stresses of pathological synovial fluid extracted from an osteoarthritic joint (intercarpal joint - OA SF) compared to the same fluid mixed with 10% (v / v) hydrogel 2% (w / v) (OA SF + 10% hydrogel 2%).

[0043] Fig.10 Shown are the shear stresses of pathological synovial fluid extracted from another osteoarthritic joint (horse tarsus) compared to the same fluid mixed with 10% (v / v) hydrogel 2% (w / v) (OA SF + 10% hydrogel).

[0044] Fig.11 The cross-linking reaction monitored by the evolution of the elastic modulus G' over time is shown for a composition according to the present disclosure (Example) and a composition comprising non-oxidized nanocrystalline cellulose (Comparative Example 1).

[0045] Fig.12 The crosslinking reaction monitored by the evolution of the elastic modulus G′ over time is shown for the same composition at 20° C. (Example) and at 40° C. (Comparative Example 2).

[0046] Fig.13 The effect of the pH of the cross-linking reaction on the elastic modulus G' of the corresponding hydrogels is shown.

[0047] Fig.14 The in vivo stability of 2% w / v hydrogels under physiological conditions over time is shown. DETAILED DESCRIPTION

[0048] The present disclosure includes a hydrogel suitable for injection into a joint to increase mobility and relieve joint pain, such as that associated with osteoarthritis. The inventors studied changes in the viscoelastic properties of synovial fluid (SF) in osteoarthritic horses and determined that in osteoarthritic joints, the rheological properties of the synovial fluid deteriorate. In particular, the synovial fluid becomes less viscous, less elastic and therefore less effective in lubricating the joint.

[0049] exist Figure 1 , the measurements of the elastic modulus (G') and viscous modulus (G") of the synovial fluid of horses in normal and pathological midcarpal joints (suffering from type I osteoarthritis) as a function of frequency are shown. It can be observed that in both orthopedic normal SF and pathological SF, the elastic component (G') dominates over the viscous component (G") for all frequency deformations. However, the absolute values ​​of G' and G" are significantly higher in the normal SF compared to the pathological SF.

[0050] When injected into an osteoarthritic joint, the hydrogel according to the present invention can restore joint lubrication, thereby improving the patient's or animal's mobility and relieving joint pain.

[0051] In addition to purified water, the hydrogel may also include at least two components: cellulose and gelatin peptide chains. However, other components such as pH buffer, growth factors, proteins, hyaluronic acid and / or polycaprolactone may be added. Alternatively or in combination, another type of polysaccharide may be used to form a hydrogel with gelatin peptide chains, such as chitosan.

[0052] Cellulose can be from biomass source or from bacteria extraction.Cellulose is preferably in the form of nanocrystalline cellulose or cellulose nanocrystal, for example does not include cellulose nanofiber.Cellulose nanocrystal can have the rod shape that comprises different faces (such as six faces), and be of a size of length 100nm to 900nm, preferably 150nm to 850nm, more preferably 240nm to 760nm, 370nm to 620nm, 410nm to 580nm and most preferably about 500nm.Crystal width and height can be 5nm to 40nm, preferably 9nm to 32nm, more preferably 10nm to 25nm and most preferably 15nm to 20nm.

[0053] Nanocrystalline cellulose can be prepared according to the following reaction 1 and Figure 2 Obtained by hydrolysis.

[0054]

[0055] exist Figure 2 In the present invention, cellulose 10 extracted, for example, from a biomass source such as cotton or from a bacterial source may contain crystalline domains and amorphous domains, and the amorphous domains may be cut by acid hydrolysis (e.g. using sulfuric acid) to obtain only the crystalline domains, preferably in the form of nanocrystals 11. Depending on the reaction conditions, nanocrystals of different shapes may be obtained, while the rod shape may provide advantageous rheological properties to the composition. In contrast to its low molecular weight homologues, nanocrystalline cellulose has limited diffusivity due to its macromolecular structure, which is advantageous for intra-articular injections.

[0056] Nanocrystalline cellulose may have terminal aldehyde reactive moieties. In addition, nanocrystalline cellulose may be functionalized to increase the number of reactive moieties or to add additional reactive moieties. Therefore, the number or type of additional reactive moieties may be different from the reactive moieties of natural and / or nanocrystalline cellulose. Preferably, the reactive moieties include C=O double bonds and are preferably aldehyde moieties. These aldehyde moieties may be obtained by oxidation of nanocrystalline cellulose, for example by oxidation with a strong oxidant such as periodate, as shown in reaction 2 below.

[0057]

[0058] According to reaction 2, the periodate ion can be attached to the two hydroxyl moieties of the cellulose sugar ring by eliminating a water molecule. The electron rearrangement results in opening the sugar ring, thereby providing a dialdehyde chain instead of a sugar ring. The reactive moiety is therefore preferably an aldehyde moiety, for example mainly or only an aldehyde moiety.

[0059] Thus, oxidation at positions C2 and C3 may lead to cleavage of sugar rings, which changes the structure of the polysaccharide chain. An increase in the flexibility of the polymer backbone may be obtained. Sterically stabilized nanocrystalline cellulose may be obtained by the oxidation step of introducing flexible units in the polysaccharide chain. The flexible units may achieve or contribute to the colloidal stability of the hydrogel. Here, the dialdehyde units formed by the oxidation reaction may be balanced with other units, such as Figure 3 Visible in.

[0060] Figure 3 represents the different rings or units of cellulose that can be formed after the above oxidation reaction. Figure 3 (a) shows the free aldehyde part, Figure 3 (b) shows the hemiacetal part in the molecule, Figure 3 (c) shows the semi-hydroxyaldehyde part, Figure 3 (d) in FIG. 4 shows a hydrated aldehyde, i.e., a hydroxyl moiety produced by hydration of an aldehyde moiety, and Figure 3 (e) shows an intermolecular hemiacetal. Figure 3 The intermolecular hemiacetals in (e) may contribute to the cross-linking between chains of nanocrystalline cellulose, but these hemiacetal bridges are rare and mostly occur between chains of the same cellulose nanocrystals.

[0061] The aldehyde content can be assessed by UV / visible spectrophotometry (BCA assay) using D-(+)-glucose as a standard. For example, the aldehyde content is 800 μmol / g to 3500 μmol / g oxidized nanocrystalline cellulose, preferably 1000 μmol / g to 2800 μmol / g, more preferably 1400 μmol / g to 2200 μmol / g and most preferably about 1900 μmol / g.

[0062] The gelatin may be any gelatin that is compatible with the human or animal species to be treated. In particular, type B gelatin may be used. The gelatin is preferably non-functionalized and may include only naturally occurring reactive moieties, such as Figure 4 Visible in.

[0063] The gelatin may comprise gelatin peptide chains, preferably obtained from bovine gelatin, as the isoelectric point of bovine gelatin is close to that of the human body. However, other types of gelatin may be used, particularly for non-human applications. Figure 4The (partial) structure of gelatin is shown, for example showing arginine, glycine and proline. However, as known to the skilled person, other natural amino acids may be present in gelatin.

[0064] The hydrogel of the present invention can be cross-linked by the reaction between oxidized nanocrystalline cellulose and gelatin peptide chains, in particular, by the reaction between the nucleophilic part of gelatin and the aldehyde part of oxidized nanocrystalline cellulose. For example, according to reaction 3, cross-linking can be achieved by Schiff base reaction.

[0065]

[0066] According to reaction 3, the ε-amine moieties of the lysine and hydroxylysine amino acids of gelatin can react with the available aldehyde moieties of the oxidized nanocrystalline cellulose, thus generating imine moieties that connect the peptide chains and sugar chains of gelatin and nanocrystalline cellulose, respectively. The reaction is preferably carried out at room temperature. In fact, room temperature allows to effectively obtain pure hydrogels ready for injection. In contrast, the inventors have found that using higher temperatures may prevent effective cross-linking reactions.

[0067] For example, the molar ratio of gelatin on oxidized nanocrystalline cellulose can be 1.8 to 0.2, preferably 1.5 to 0.5, more preferably 0.8 to 1.2, most preferably 1. The degree of crosslinking can be defined as the ratio of the amount of imine moiety in the hydrogel to the amount of aldehyde moiety on the oxidized cellulose before forming the hydrogel. The degree of crosslinking can be up to 70% or up to 60%, preferably 38% to 55%, more preferably 45% to 53%, for example about 49%. Such a degree of crosslinking allows for good injectability.

[0068] The hydrogel of the present invention can be a fluid gel. For example, in 0.1s -1 At a shear rate of and after 100s, the viscosity of the hydrogel can be 100Pa.s-500Pa.s.

[0069] Rheological analysis

[0070] The rheological behavior was studied on an Anton Paar Modular Compact Rheometer MCR 302e. A plate-plate geometry (PP25) with a gap of 0.5 mm was used. The properties of the samples were checked at the physiological temperature of the horse (i.e. 37.5°C) with an accuracy of 0.1°C provided by the instrument's Peltier plate temperature control system.

[0071] Oscillation Testing and Viscoelasticity

[0072] The viscoelastic properties of the samples were determined via dynamic experiments. Storage modulus (or elastic modulus) (G'), loss modulus (or viscous modulus) (G"), loss tangent (tan δ) and complex viscosity (η*) were monitored as a function of frequency.

[0073] The loss tangent (tanδ) is defined according to Equation 1.

[0074]

[0075] The complex viscosity η* is a measure of the total resistance to flow as a function of the angular frequency (ω) and is given by the quotient of the maximum stress amplitude and the maximum strain rate amplitude.

[0076] Dynamic strain sweep testing was also performed as follows: At a fixed frequency, a strain sweep from 0.1% to 100% was applied to determine the linear viscoelastic range. Dynamic frequency sweep testing: The strain constant was held at 10% and a frequency sweep from 0.1 Hz to 4 Hz was applied. The frequency range studied covered the physiological frequencies of knee motion (0.5 Hz, rising to 3 Hz for slower knee motions).

[0077] Spin Test and Viscosity

[0078] In 0.01s -1 The synovial fluid samples were rotated and the viscosity was measured at a constant shear rate of 100 s. -1 The pre-shear is applied for 60 seconds, and t = 0 is the time between the end of the pre-shear and the start of the 0.01s application during the 600 seconds. -1 Shortly thereafter. The shear stress τ is calculated according to Equation 2, where F is the shear force (in N) and A is the shear area A (in m 2 count).

[0079]

[0080] For the 2.0% w / v injectable hydrogel, the viscoelastic properties (loss G" and elastic G' modulus) as a function of frequency are shown in Figure 5 , while the frequency dependence of complex viscosity and tan δ is reported in Figure 6 The rheological behavior of the hydrogel of the present invention is a typical weak gel. In the entire frequency range, the elastic modulus (G') is always about one order of magnitude higher than the viscous modulus (G"), and both moduli are independent of frequency.

[0081] Furthermore, from 0.1 Hz to 10.0 Hz, the elastic modulus G' is always greater than 10 Pa, preferably greater than 50 Pa and more preferably greater than 80 Pa. In the same frequency range, the loss modulus G" is always lower than 10 Pa, preferably lower than 9 Pa.

[0082] about Figure 6 , the loss factor (tanδ) is equal to or greater than 10 at 0.1Hz 5 , equal to or greater than 10 at 1Hz 4 And at 10Hz it is greater than 10 3 Therefore, in the frequency range of 0.1Hz to 10Hz, the loss factor can be 10 3 Up to 10 5 The complex viscosity can be 10 -2 Between mPa.s and 1 mPa.s, preferably 0.2 mPa.s to 0.8 mPa.s, more preferably about 0.1 mPa.s.

[0083] In vitro results

[0084] In order to demonstrate the healing properties of the hydrogel of the present invention on arthritic joints, a mixture of the hydrogel of the present invention at a concentration of 2% (w / v) in PBBS buffer and horse synovial fluid (10% volume of hydrogel in pathological synovial fluid, i.e. 1 ml of hydrogel in 9 ml of synovial fluid) has been studied in order to simulate what occurs in vivo after injection. Figure 7 The elastic (G') and viscous (G") moduli from pathological synovial fluid (OASF) and pathological synovial fluid mixed with 10% of the above hydrogel (v / v) (i.e., 1 ml hydrogel in 9 ml pathological synovial fluid) are shown as a function of frequency. Figure 7 As shown, the viscoelastic modulus values ​​of pathological synovial fluid (OA SF) increased for all deformation frequencies when mixed with the hydrogel of the present invention.

[0085] Figure 8 The elastic (G') and viscous (G") moduli of pathological synovial fluid mixed with 10% hydrogel 2.0% (w / v) and normal synovial fluid (normal SF) are shown as a function of frequency, both extracted from the intercarpal joint of a horse. This experiment allows to simulate a pathological joint healed by the hydrogel of the invention with respect to a normal joint. The values ​​of the elastic (G') and viscous (G") moduli of the pathological synovial fluid mixed with the hydrogel of the invention are close to or similar to the values ​​obtained by the synovial fluid of a normal healthy joint. These results allow to conclude that the hydrogel of the invention can be successfully injected into pathological joints suffering from osteoarthritis in order to relieve pain and at least partially restore mobility.

[0086] The shear stress τ as a function of time for pathological synovial fluid and pathological synovial fluid mixed with 10% (v / v) of the hydrogel of the present invention at 2.0% (w / v) is shown in Fig. 9 middle. Fig. 9 It is shown that both samples exhibit very close shear stress values ​​and rheological behavior defined as the increase in shear stress with time at a constant shear rate.

[0087] Fig.10 is Figure 7 The results of the same experiment conducted in , but using synovial fluid from a different joint: the equine tarsal joint. Both moduli of the pathological synovial fluid are low, while the loss modulus G" drops rapidly above 1 Hz (i.e., fast walking and running). In contrast, both moduli increase when mixed with the 10% (v / v) hydrogel 2% (w / v) of the present invention. At low frequencies (i.e., walking), the mixed synovial fluid retains its viscous characteristics, while at higher frequencies (running), the mixed synovial fluid tends to retain its elastic properties, thereby potentially protecting the articular cartilage from unmitigated forces.

[0088] Then, detailed examples of procedures that can be used to obtain the hydrogels of the present invention are provided below. These procedures do not limit the above general disclosure, but are provided to enable a full disclosure.

[0089] Preparation of Oxidized Nanocrystalline Cellulose

[0090] In a 1L two-necked flask, 300ml of demineralized water was added and acidified to pH 3.0 with 5.5ml of acetic acid (36%). Under mechanical stirring, 6.0g of cellulose nanocrystals were suspended. 92.5ml of 0.7M NaIO4 solution was added dropwise to the mixture. The flask was protected from light, and the mixture was reacted at 45°C for 4 hours.

[0091] Ethylene glycol (5.0 ml) was added to stop the reaction, the pH was adjusted to 6.0 with Na2CO3 (1 M, 17.3 ml) and stirred for another hour. The final mixture was dialyzed (SpecPor 5, 12 kDa-14 kDa) against water (28 L) at room temperature for 5 days with 3 changes of water until a total dissolved solids content (TDS) of 0 ppm was obtained.

[0092] 2.0% (w / v) Hydrogel Preparation Example

[0093] 3.2 ml of dialdehyde nanocrystalline cellulose (aldehyde content: 1891 μmol / g) suspension was diluted to a total volume of 10 ml in pyrogen-free water. 170 mg of type B gelatin (primary amine content: 435 μmol / g) was diluted in pyrogen-free water at 37°C and then cooled to 20°C. The diluted gelatin was added to the dialdehyde nanocrystalline cellulose together with 96 mg of Dulbecco's phosphate buffered saline (DPBS) at a temperature of 20°C to buffer the solution to a pH of 7.2-7.4. No stirring was performed during crosslinking.

[0094] The cross-linking reaction is complete after 20 hours at room temperature, thereby obtaining a viscoelastic hydrogel. The hydrogel can be kept at a temperature of 15°C-25°C during storage and then sterilized with gamma radiation, such as 30 kGy, i.e., at least 25 kGy of C 60Gamma source. The efficacy of the cross-linking reaction (Schiff base reaction) was assessed by TNBS assay, whereby the concentration of primary amines was determined. Alternatively, an acid-base titration with hydroxylamine was also performed. Based on this data, we can conclude that all aldehydes reacted quantitatively with amines and resulted in a 49.9% degree of gelatin cross-linking.

[0095] Determination of aldehyde groups in oxidized nanocrystalline cellulose using the BCA method

[0096] The oxidized nanocrystalline cellulose sample was diluted to 0.01% concentration with BCA buffer (1.0M KCl; 0.01M Na2CO3; 0.09M NaHCO3). For the calibration curve, 0.09008g D-(+)-glucose was dissolved in a 500ml volumetric flask with BCA buffer to obtain a 1000μM D-(+)-glucose stock solution. A standard series was prepared by diluting the stock solution with the following concentrations: 0μM, 50μM, 100μM, 250μM, 500μM. Process the standards, such as the diluted samples. Transfer 100μL of the diluted sample / standard to a covered glass vial and add 900μL of BCA buffer. Then, 1000 μL of freshly prepared BCA reagent solution (0.2561 M Na2CO3; 0.1440 M NaHCO3; 0.0025 M BCA; 0.0039 M CuSO4·5H2O; 0.0060 M) was added. The glass vial was then heated at 75°C in a water bath for 30 minutes. The absorbance was measured at a wavelength of 560 nm relative to softened H2O in a double beam spectrophotometer.

[0097] The aldehyde content is preferably 1500 to 2500 μmol / g nanocrystalline cellulose, preferably 1700 to 2300 μmol / g, more preferably 1800 to 1900 μmol / g.

[0098] Determination of free primary amino groups in cross-linked hydrogel samples using the TNBS method

[0099] 10 μL of sample was transferred to an amber glass vial with a screw cap, 990 μL of TNBS buffer (0.1 M NaHCO3; pH 8.5) was added, and the gelatin concentration of the diluted sample was about 0.01% (w / v). In order to draw a calibration curve, a stock solution was prepared by weighing 0.0563 g of L-glycine with an analytical balance and dissolving it in a 500 ml volumetric flask with TNBS buffer to a final concentration of 1500 μM of L-glycine. The stock solution was then diluted with TNBS buffer to prepare a standard series with the following concentrations: 10 μM, 25 μM, 50 μM, 75 μM, 100 μM, 150 μM. For each standard, 1000 μL was transferred to an amber glass vial with a screw cap and treated in the same manner as the sample.

[0100] The amine content is preferably 220 μmol / g to 840 μmol / g of gelatin peptide chain, preferably 350 μmol / g to 520 μmol / g, most preferably 390 μmol / g to 450 μmol / g.

[0101] Freshly prepare 0.05% TNBS solution by diluting 5% TNBS with TNBS buffer. Add 500 μL of freshly prepared 0.05% TNBS solution to each vial. Incubate the solution in an oven at 37°C for 2 hours. After incubation, add 250 μL 1M HCL and 500 μL softened H2O to stop the reaction in each vial. Then all solutions are hydrolyzed in an autoclave at 120°C and about 15psi (103421Pa) for 1 hour. After hydrolysis, transfer about 2 ml of solution to a UV cuvette with a path length of 1 cm and measure at a wavelength of 335 nm relative to a blank prepared similarly to the sample in a double beam spectrophotometer.

[0102] Cross-linking reaction

[0103] In order to study the efficiency of the cross-linking reaction, a first composition ( Fig.11 ), and a second composition comprising the above-mentioned gelatin peptide chains and non-oxidized nanocrystalline cellulose (i.e., comprising only naturally occurring aldehyde moieties) has been prepared ( Fig.11 Comparative Example 1 in ). Both compositions were incubated at 20° C. without stirring and the elastic modulus of both compositions was studied over time (ie up to 25 hours).

[0104] like Fig.11 As can be seen in the figure, the elastic modulus G' of Comparative Example 1 increases slightly over time, indicating physical gel formation. In contrast, the elastic modulus G' of Example (i.e., the inventive hydrogel 2% w / v) increases strongly over time, indicating physical gel formation and effective crosslinking. Therefore, the use of oxidized nanocrystalline cellulose allows the appropriate rheological and mechanical properties of the inventive hydrogel to be obtained through effective crosslinking.

[0105] Then, a second experiment was conducted to determine the effect of temperature on the crosslinking reaction. The increase in elastic modulus G' over time of the first composition as described above and a third composition identical to the first composition has been studied. The first composition was incubated at 20°C without stirring ( Fig.12 ), while the third composition was incubated at 40°C ( Fig.12 Comparative Example 2).

[0106] like Fig.12As can be seen, the elastic modulus G' of Comparative Example 2 did not increase over time, indicating no crosslinking or very limited crosslinking. In contrast, the elastic modulus G' of Example (i.e., the hydrogel 2% w / v of the present invention) increased strongly over time, indicating effective crosslinking. Therefore, the optimal temperature for effective crosslinking is 15°C to 25°C, preferably about 20°C.

[0107] The effect of pH on the cross-linking reaction was then investigated taking into account the elastic modulus G' obtained at 20°C for the resulting hydrogel (2% w / v). When a primary amine moiety reacts with an aldehyde or ketone moiety under appropriate conditions, an imine moiety is formed. The formation of imines generally requires an acid catalyst. Acid catalysts allow the removal of water. On the other hand, the mechanism involves a nucleophilic attack of an unprotonated amine on a carbonyl functional group.

[0108] Fig.13 The elastic modulus (G') of 2% w / v hydrogels obtained by cross-linking reaction in different pH buffers and at different reaction times (0 to 25 hours) is shown. The elastic modulus was measured as disclosed above. For pH 6.0 and 7.0, higher elastic moduli were obtained after only 10 hours of reaction. At a given reaction time, the cross-linking reaction in phosphate buffer at pH = 6.0 resulted in a hydrogel with a higher elastic modulus than pH = 7.0, which supports the fact that weakly acidic conditions favor imine formation.

[0109] For the hydrogels obtained at pH = 8, a strong increase was shown at the beginning (< 5 hours), but the elastic modulus G' subsequently flattened out, which may be due to the alkaline degradation of the hydrogel. For the hydrogels obtained at pH = 5, the cross-linking reaction has a limited rate, and although the elastic modulus increases with reaction time, it cannot match the elastic modulus obtained for the hydrogels obtained at pH = 6 or 7 given a reaction time of more than 5 hours. Considering the desired elastic modulus G', the optimal pH for the cross-linking reaction may be 6.0 to 7.5. A cross-linking pH of 7.4 allows obtaining gels with a high cross-linking rate under physiological conditions, thus avoiding an additional step of changing the pH of the hydrogel.

[0110] In vitro toxicity

[0111] In vitro cytotoxicity tests were performed according to the method of ISO 10993-5:2009 on dialdehyde nanocrystalline cellulose, nanocrystalline cellulose, and 1.0 (w / v)% and 2.0 (w / v)% of the hydrogel of the present invention as shown in Table 1. This shows that, compared with dialdehyde nanocrystalline cellulose, the hydrogel of the present invention has no cytotoxic effect and can be safely injected.

[0112] sample Decreased cell viability (%) result Nanocrystalline cellulose 12±0.76 Non-cytotoxic Dialdehyde Nanocrystalline Cellulose 88±0.76 Cytotoxicity Hydrogel 1.0% 6±0.76 Non-cytotoxic Hydrogel 2.0% 12±0.76 Non-cytotoxic

[0113] [Table 1]

[0114] Miscibility

[0115] Body joints are filled with synovial fluid, and miscibility is a key criterion for evaluating the ability of a hydrogel to treat joints with OA.Synovial fluid is primarily composed of water, hyaluronic acid, lubricin, proteases, collagenases, and prostaglandins and has a pH of approximately 7.5.

[0116] Injecting an immiscible hydrogel into a damaged joint to be treated may provide no benefit or only limited benefit in terms of pain and mobility, but may trigger a strong inflammatory response, thereby degenerating the treated joint. Therefore, the miscibility of the hydrogel of the present invention has been evaluated under physiological conditions (i.e. PBS buffer, pH=7.4, temperature of 37°C) and compared with the miscibility of the comparative hydrogel described below. The results of this evaluation are visible in Table 2.

[0117] Table 2

[0118] sample Miscibility Hydrogel 1% w / v Stable colloid Hydrogel 2% w / v Stable colloid Hydrogel 4% w / v Stable colloid Comparative Example 3 not applicable Comparative Example 4 Immiscible Comparative Example 5 Immiscible

[0119] The hydrogels of the present invention are completely miscible under physiological conditions and form stable colloids at concentrations of 1% to 4% w / v. The same miscibility results were observed in horse synovial fluid (see above rheology and viscoelastic experiments). Without being bound by any theory, it is believed that the unique chemical structure of the hydrogel allows for a stable colloid to be obtained in PBS buffer and synovial fluid, thereby obtaining a single phase with favorable viscoelastic and rheological properties.

[0120] Comparative Examples

[0121] Comparative Example 3 was obtained by replacing gelatin with collagen in the above method for preparing a hydrogel. The conditions for the cross-linking reaction between collagen and oxidized nanocrystalline cellulose were a temperature of 20° C. without stirring for 10 hours. No cross-linking reaction was performed under the above conditions, and no hydrogel was obtained.

[0122] Comparative Example 4 relates to a hydrogel prepared according to Example 3 of CN110760103. The hydrogel was prepared by mixing oxidized nanocrystalline cellulose at a concentration of 12 mg / ml and pH=8 with the same weight of a prepolymerized collagen solution at a concentration of 12 mg / ml and pH=5 in a container. A viscous hydrogel was obtained after slow mixing at room temperature for half a minute. However, the hydrogel of Comparative Example 4 was not miscible in PBS buffer at pH=7.4 or in synovial fluid, and two different phases were obtained. Therefore, rheological measurements as described above could not be performed.

[0123] The hydrogel of Comparative Example 4 was evaluated in vivo. The 2% w / v hydrogel of Comparative Example 4 was subcutaneously injected into mice, and no inflammatory response was observed. Then, the same 2% hydrogel was injected into three hoof joints with OA, and a strong inflammatory response was observed. Therefore, it is clear that the hydrogel of Comparative Example 4 cannot relieve the symptoms of joints with OA.

[0124] Comparative Example 5 relates to preparing a hydrogel using the method of the present invention and replacing oxidized nanocrystalline cellulose with oxidized carboxymethyl cellulose. Under the above cross-linking reaction conditions, a hydrogel was obtained. However, this hydrogel was immiscible in a PBS buffer at pH = 7.4 and was immiscible in synovial fluid. Therefore, the hydrogel of Comparative Example 5 could not relieve the symptoms of damaged joints.

[0125] Comparative Example 6 relates to a cross-linking reaction between oxidized nanocrystalline cellulose and gelatin according to the present method. However, the cross-linking conditions were changed to 37°C in a PBS buffer at pH = 7.4. No cross-linking was obtained under these conditions, and no hydrogel was formed. Without being bound by any theory, it is believed that the reaction rate of β-elimination is greater than the reaction rate of Schiff base formation, thus preventing an effective cross-linking reaction.

[0126] In vitro stability

[0127] The in vitro stability of 2% w / v hydrogels was studied under physiological conditions for more than 6 months. Six 2% w / v hydrogel samples were prepared and kept at 37°C and pH=7.4 under gentle shaking. In order to determine the weight of the hydrogel of each sample, the sample was freeze-dried to remove the liquid phase and the weight (wt) of the gel portion was obtained from a precision balance. After 2 months, the remaining weight was still higher than 90% of the initial weight (wo). After 6 months, there was still about 20% of the initial weight (wo).

[0128] Therefore, this preliminary stability experiment demonstrated the good stability of the hydrogel under physiological conditions, thereby supporting the long-term relief of OA symptoms in vivo.

[0129] Dosimetry

[0130] Small horse joints can be treated with 2 ml of 2% w / v hydrogel, while large horse joints can be treated with 4 ml of 2% w / v hydrogel. For human joints, 1 ml of 2% w / v hydrogel can be used.

[0131] While the present invention has been described and illustrated in detail, it is to be clearly understood that the present invention has been presented by way of illustration and example only and is not to be construed in a limiting sense, the scope of the present invention being limited solely by the terms of the appended claims.

Claims

1. An injectable hydrogel, comprising: ●Oxidized nanocrystalline cellulose, ● Gelatin peptide chain, The oxidized nanocrystalline cellulose and the gelatin peptide chains are cross-linked.

2. The injectable hydrogel according to the preceding claim, wherein the oxidized nanocrystalline cellulose and the gelatin peptide chains are cross-linked via imine moieties.

3. An injectable hydrogel according to any one of the preceding claims, wherein the gelatin peptide chains have a concentration of 1.0 weight / volume % to 2.5 weight / volume % before cross-linking, and / or the oxidized nanocrystalline cellulose has a concentration of 0.1 weight / volume % to 0.5 weight / volume % before cross-linking.

4. The injectable hydrogel according to any one of the preceding claims, wherein the injectable hydrogel comprises 0.5% to 2.5% by weight / volume of cross-linked oxidized nanocrystalline cellulose and gelatin peptide chains.

5. The injectable hydrogel according to any one of the preceding claims, wherein the injectable hydrogel has an elastic modulus of 10 Pa to 220 Pa at 0.1 Hz to 10.0 Hz.

6. An injectable hydrogel according to any one of the preceding claims, wherein the injectable hydrogel has a loss modulus below 10 Pa at 0.1 Hz to 10.0 Hz.

7. An injectable hydrogel according to any one of the preceding claims, wherein the injectable hydrogel has a frequency of greater than 10 at 0.1 Hz. 5 The ratio of the loss modulus to the elastic modulus (tanδ).

8. The injectable hydrogel according to any one of the preceding claims, wherein the complex viscosity of the injectable hydrogel is below 1.0 mPa.s at 0.1 Hz to 10.0 Hz.

9. The injectable hydrogel according to any one of the preceding claims, wherein the injectable hydrogel has a degree of cross-linking of 25% to 60%, preferably 38% to 49%.

10. A method for preparing an injectable hydrogel according to any one of the preceding claims, the method comprising the steps of: - Dilute oxidized nanocrystalline cellulose in pyrogen-free water - Add gelatin peptide chains to diluted oxidized nanocrystalline cellulose at room temperature - reacting the gelatin chains with the oxidized nanocrystalline cellulose.

11. The method for preparing an injectable hydrogel according to claim 9, wherein the reaction step is performed for 10 hours to 25 hours, preferably at a temperature of 15°C to 25°C.

12. A method of preparing an injectable hydrogel according to claim 9 or claim 10, wherein the reacting step is carried out at a pH greater than 7 and at most 8.

13. The method for preparing an injectable hydrogel according to any one of claims 9 to 11, further comprising the steps of diluting the gelatin peptide chain in water at 37°C and cooling the diluted gelatin peptide chain at room temperature.

14. Use of an injectable hydrogel according to any one of claims 1 to 9 for treating or alleviating the symptoms of osteoarthritis.

15. A syringe comprising the hydrogel according to any one of claims 1 to 9.